Protective Effects of Vitamin C against Neomycin-Induced Apoptosis in HEI-OC1 Auditory Cell - Liang Gong; Biao Chen; Jingyuan Chen; Yongxin Li (Neural Plasticity)
Ototoxic hearing loss results from hair cell death via reactive oxygen species (ROS) overproduction and consequent apoptosis. We investigated the effects of vitamin C (VC) on neomycin-induced HEI-OC1 cell damage, as well as the mechanism of inhibition. HEI-OC1 cells were treated with neomycin or with vitamin C (VC). The results indicated that VC had a protective effect on neomycin-induced HEI-OC1 cell death. Mechanistically, VC decreased neomycin-induced ROS generation, suppressed cell death, and increased cell viability. VC inhibited neomycin-induced apoptosis, ameliorated neomycin reduced antiapoptotic Bcl-2 expression, and suppressed neomycin increased expression of proapoptotic Bax, caspase-3 cleavage and caspase-8. TUNEL labeling demonstrated that VC blocked neomycin-induced apoptosis. Further study revealed that the effect of VC on neomycin-induced hair cell death was through interference with JNK activation and p38 phosphorylation. These results indicate that VC via suppressed ROS generation, which inhibited cell death by counteracting apoptotic signaling induced by neomycin in cells. Hence, VC is a potential candidate for protection agent against neomycin-induced HEI-OC1 cell ototoxicity.